Impact of Style of Daagh on Poetry of Ashk and Dewaan e Ashk - Dr. Mohammad Shah Khaga; Dr. Rukhsana BiBI; Dr. Mutahir Shah; Muhammad Farooq Baig (Zaban-o-Adab, 2021)
The full name of Ash’k Rampuri is Nawabzada wajid Ali khan Ash’k Rampuri.Ash’k was born in Ram-Pur.Ram-Pur was a small state but its literary level was a very high.Even,it should be called as school of manners of Urdu-literature.Ash’k read Urdu and Persian,and due to this he was inclined towards Sufism.He had great love for Sufism and Qadari chain.These was deep pain and erethism in his nature.He was embodiment of separation and pain.It seems that someone who was near and dear to him was aparted.He abandoned all the matters of life and preffered to live life of a sufi.He spent his remaining life in Golra Sharif. Keywords:Nawabzada, Rampur, Wajid Ali Khan, Persian, Qadari chain, Sufism, pain, England, Golra Sharif.